Differential Requirement of Gata2a and Gata2b for Primitive and Definitive Myeloid Development in Zebrafish - Peña, Oscar A.; Lubin, Alexandra; Rowell, Jasmine; Hoade, Yvette; Khokhar, Noreen; Lemmik, Hanna; Mahony, Christopher; Dace, Phoebe; Umamahesan, Chianna; Payne, Elspeth M. (Frontiers in Cell and Developmental Biology, 2021)
Germline loss or mutation of one copy of the transcription factor GATA2 in humans leads to a range of clinical phenotypes affecting haematopoietic, lymphatic and vascular systems. GATA2 heterozygous mice show only a limited repertoire of the features observed in humans. Zebrafish have two copies of the Gata2 gene as a result of an additional round of ancestral whole genome duplication. These genes, Gata2a and Gata2b, show distinct but overlapping expression patterns, and between them, highlight a significantly broader range of the phenotypes observed in GATA2 deficient syndromes, than each one alone. In this manuscript, we use mutants for Gata2a and Gata2b to interrogate the effects on haematopoiesis of these two ohnologs, alone and in combination, during development in order to further define the role of GATA2 in developmental haematopoiesis . We define unique roles for each ohnolog at different stages of developmental myelopoiesis and for the emergence of hematopoietic stem and progenitor cells. These effects are not additive in the haploinsufficient state suggesting a redundancy between these two genes in hematopoietic stem and progenitor cells. Rescue studies additionally support that Gata2b can compensate for the effects of Gata2a loss. Finally we show that adults with loss of combined heterozygosity show defects in the myeloid compartment consistent with GATA2 loss in humans. These results build on existing knowledge from other models of GATA2 deficiency and refine our understanding of the early developmental effects of GATA2. In addition, these studies shed light on the complexity and potential structure-function relationships as well as sub-functionalisation of Gata2 genes in the zebrafish model.